2010
DOI: 10.1108/00021461011064950
|View full text |Cite
|
Sign up to set email alerts
|

Cost evaluation of alternative switchgrass producing, harvesting, storing, and transporting systems and their logistics in the Southeastern USA

Abstract: Purpose -The US Department of Energy has a goal to make ethanol from biomass cost competitive with petroleum by 2012. Feedstock procurement is expected to represent a significant portion of the operating costs for a refinery that produces ethanol from biomass such as switchgrass. Thus, costeffective feedstock logistics will be a key factor for the future development of a capital intensive cellulosic ethanol industry. The purpose of this paper is to analyze the cost of various logistic methods of switchgrass pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…An extended harvest season would require fewer harvest machines per biorefinery thereby reducing overall harvest machinery fixed costs (Epplin and Haque, 2011; Haque and Epplin, 2012). An extended harvest window would enable a just‐in‐time delivery system during harvest months and reduce overall storage cost (Cundiff and Marsh, 1996; Larson et al, 2010; Grisso et al, 2013). However, with an extended harvest window, the expected harvestable yield and the expected fertilization requirement for the succeeding year might differ depending on the harvest date.…”
mentioning
confidence: 99%
“…An extended harvest season would require fewer harvest machines per biorefinery thereby reducing overall harvest machinery fixed costs (Epplin and Haque, 2011; Haque and Epplin, 2012). An extended harvest window would enable a just‐in‐time delivery system during harvest months and reduce overall storage cost (Cundiff and Marsh, 1996; Larson et al, 2010; Grisso et al, 2013). However, with an extended harvest window, the expected harvestable yield and the expected fertilization requirement for the succeeding year might differ depending on the harvest date.…”
mentioning
confidence: 99%
“…Losses for bales stored inside were negligible. Larson et al [22] found storage dry matter losses of 30% for rectangular solid bales of switchgrass that were covered with a tarp and stored for 360 days. They estimated storage cost to be 6 $ Mg À1 y À1 for tarp and pallet and 12 $ Mg À1 y À1 for tarp and gravel.…”
Section: Storage Cost and Storage Lossesmentioning
confidence: 99%
“…Upwards of $100 is estimated for one truck transporting biomass a distance of 60 km from farm to refinery (Brechbill et al 2011). An approach to reducing transportation cost could involve preprocessing locally at regional centers, but this is envisioned as being limited to mechanical preparation of the biomass such as cleaning, comminution, and packaging (Larson et al 2010). A feedstock cooperative among farmers could provide economies in use of equipment and provide employment during seasons when the biomass is not grown.…”
Section: Introductionmentioning
confidence: 99%